PROBLEMATIKA PERLINDUNGAN UPAH PEKERJA PADA UNIT USAHA DESA ADAT (BAGA UTSAHA PADRUEN DESA ADAT) DALAM PERSPETIF UNDANG-UNDANG NO 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Ida Bagus Brahma Kusuma; I Wayan Gde Wiryawan; I Wayan Eka Artajaya, (Jurnal Hukum Saraswati (JHS), 2025)
Indonesia as the 5th largest population country in the world, Indonesia has a very large labor force. Labor dynamics are very interesting to study and research more deeply because as a large population in Indonesia has switched, which used to make a living as a farmer but now more are working in the industrial sector which often causes many problems that have no end. The 1945 Constitution of the Republic of Indonesia in Article 27 paragraph (2) stipulates that “Every citizen has the right to a job and a livelihood worthy of humanity”. This provision raises issues related to the dilemma of workers with the concept of ngayah in the protection of workers' wages in the customary village business unit of the customary village? This arises from the phenomenon of dilemma between the concept of ngayah and the perspective of labor law. The concept of ngayah is a very principle thing by indigenous peoples on the basis of sincere values, which of course must get legal protection by the government against businesses that are done to produce in this case the business of baga utsaha padruen traditional village which oversees traditional village tourism with the management of the traditional village itself.